Closing Doors and Opening Gates: Professor Ruggles Gates, “Race Crossing” Research, and the Strange Survival of Scientific Racism in Post-war Australia - Brown Robert (HoST)
In 1958, botanist-biologist Professor Reginald Gates conducted biometric and anthropometric “race crossing” studies on populations spanning Australia and Papua New Guinea. Gates is largely remembered as an anachronistic conservative whose opposition to interracial marriage and belief in race theory ostracised him from the post-war Anglo-American scientific mainstream. Paradoxically, the article aims to investigate the more positive responses that Gates, funded by segregationist American benefactors, received from Australian anthropologists interested in aiding his research. It argues Gates’ activity throughout the Global South, and the methodological overlap and collaboration he experienced with Australian anthropologists, further complicates and decentres North Atlantic facing understandings of the decline of racial thinking after 1945. Gates resurrected the legacy of the abortive Harvard-Adelaide “race-crossing” study (1938-39), in order to manufacture a tranche of data that would help serve his scientific insurgency against the UNESCO statements on racial equality (1950). Leaning on reminiscences of Harvard-Adelaide anthropologists Joseph Birdsell and Norman Tindale, Gates determined that by re-treading their footsteps, he could buttress his thesis that “races” were segregated by nature. The article demonstrates that using Australian fieldwork, he advanced his regressive political agenda that population groups, in the United States and elsewhere, should be segregated by political design. As an associate editor of the scientific racist Mankind Quarterly journal, Gates bypassed mainstream channels to disseminate his miscegenation research.